History of Pharmaceutical Development in Nepal - Khanal, Dharma Prasad (Journal of Manmohan Memorial Institute of Health Sciences, 2018)
The historical event of the development of pharmacy was started during ancient Lichchhavi ruler Amshu Berma date back to 605-620 AD when a Ayurvedic hospital was established. In 1641-1674 AD, King Pratap Malla started ayurvedic medicine production unit in the royal place. Modern allopathic medicines were introduced in Nepal in 1816 AD after Suguali Treaty and establishment of British residency in Nepal. Allopathic medicine manufacturing was started in 1969 in private sector and a government undertaking Royal Drug Limited was established in 1972.  Department of Drug Administration (DDA), a drug regulating Agency of the country was established according to the Drug Act in 1979. The pharmaceutical education was started in Nepal with the commencement of the Proficiency Certificate Level, a two and half year program (Intermediate in Pharmacy that is similar to Diploma of Pharmacy) at the Institute of Medicine, Tribhuban University in 1972. Santabhavan Hospital (present patan Hospital that was established in 1956) is pioneer to start hospital Pharmacy service in Nepal followed by Tansen Mission hospital Palpa that was started operation in 1959.Journal of Manmohan Memorial Institute of Health SciencesVol. 3, No. 1, 2017, page: 86-93